A New Species of Mimosa L. ser. Bipinnatae DC. (Leguminosae) from the Cerrado: Taxonomic and Phylogenetic Insights - Morales, Matias (2020)
Mimosa carolina (Leguminosae), a new species from the Parque Nacional Chapada das Mesas, located in the northern limit of the Brazilian Cerrado, is described and illustrated. In addition, a phylogenetic reconstruction was performed to recover the position of this species in relation to the main clades of the genus Mimosa. This new species is assigned to sect. Habbasia ser. Bipinnatae and exhibits relevant morphological differences with all described species of this series, most notably the prostate habit, glabrous stems, and absence of internal spicules. Our results indicate that this new entity is clearly nested in a strongly supported clade with other striated-corolla species of ser. Bipinnatae. Therefore, ser. Bipinnatae appears to be monophyletic, and a morphologically and ecologically cohesive group within Mimosa. An updated identification key for this series is provided.